Apartment Façade Design Characteristics for Middle and Upper Occupants with Ecological Design Approach - Yoga Pramatatya; Vincentius Totok Noerwasito; Arina Hayati (Institut Teknologi Sepuluh Nopember, 2020)
Social and economic conditions affect people’s behavior and preference for housing and the selection of housing area and its design. People with higher economic and social conditions will choose a better quality of housing and the environment. This decision also influences housing preference for apartment design. The quality of the apartment is influenced by a healthy environment, the use of energy that is efficient and can be recycled, using the eco-design approach, and basic facilities are provided. This study focuses on design-based research for designing an apartment building that suits the preferences of middle and upper occupants with an ecological approach. In this study, middle and upper occupant preference determines the shape of the facade design in buildings. In order to determine design parameters and criteria, this study uses a literature review, data analysis, and architectural precedent study. The result finds that several aspects are synthesized and selected as general design criteria apartment buildings. The important parameters in the design of the facade of the building are attractive façade design and emphasize the changing color through vegetation design inside and surrounding the building facades at each season. The building is designed minimalist architecture with a neutral color selection that is combined with natural colors such as wood and stone. Parts of apartment facilities can also be accessed by the occupants easily. Placement of vegetation evenly gives the impression of being close to nature and provides relaxation for each occupant of the apartment building.